EKSPERIMEN MENGGAMBAR DENGAN TEKNIK TEMPEL MONTASE PADA ANAK-ANAK DI PAUD INTAN KABUPATEN LANGKAT - Putri Pebi Rezika; Azmi Azmi (Universitas Negeri Medan, 2020)
The aim of this study were to know how the process and stages to be carried out in experimental drawing with montage paste technique by the students in PAUD Intan Kecamatan Kuala Kabupaten Langkat. To figure out the result of drawing by using montage paste technique in terms of accuracy of cutting, accuracy of sticking, and accuracy of neatness in PAUD Intan Kecamatan Kuala Kabupaten Langkat. The kind of this research is experiment research. The methodology of this study is descriptive qualitative research. The population of this study were 2 experimental drawing with montage paste technique. The sample used in this study is the saturation or total sample technique. The assessment indicators are in terms of accuracy of cutting, accuracy of sticking, and accuracy of neatness. The results showed that overall of the experimental results of drawing with montage paste technique was 74.99 with category B (developing in expectation). Accuracy of cutting gets category B (developing in expectation), accuracy of sticking gets category B (developing in expectation), accuracy of neatness gets category B (developing in expectation)Keywords : Experiment, Drawing, Montage Paste Technique